Implementation of the Jigsaw Type Cooperative Learning Method in Increasing Student Learning Activity in Islamic Cultural History Subjects - Abdillah, Zuhdi; Saihan, Saihan; Muhith, Abd.; Rahman, Yudi Ardian (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2024)
This study aims to analyze the effectiveness of implementing the Jigsaw cooperative learning method in improving students' engagement, collaboration, understanding, and retention in the subject of Islamic Cultural History (IHR). The study also identified the challenges faced during the implementation of the method, such as students' adaptation to new roles, ability variation, time management, and group dynamics. The research was conducted through a Classroom Action Research (PTK) approach in several cycles, involving observations, interviews, and analysis of student learning outcomes. The results showed that the Jigsaw method significantly increased student engagement, build teamwork, and strengthened social skills, such as communication and conflict resolution. Data showed an increase in material comprehension and long-term retention through collaborative interaction and group discussion. The study also identified implementation challenges, such as students' initial resistance to active roles, uneven contributions within groups, and time management constraints. Mitigation strategies, such as gradual guidance, provision of additional materials, and structured time management, proved effective in overcoming these obstacles. This study makes a practical contribution to the educational literature by confirming the effectiveness of the Jigsaw method while offering solutions to implementation challenges. The implications of this study suggest that the active role of teachers is crucial in ensuring the success of this method, as well as encouraging the application of the Jigsaw method in broader and diverse educational contexts. This research also opens up opportunities for further exploration of the application of the Jigsaw method in other subjects and groups of students with special needs.